Disturbances, organisms and ecosystems: a global change perspective. Issue 4 (6th March 2013) - Ponge, Jean‐François
Abstract: The present text exposes a theory of the role of disturbances in the assemblage and evolution of species within ecosystems, based principally, but not exclusively, on terrestrial ecosystems. Two groups of organisms, doted of contrasted strategies when faced with environmental disturbances, are presented, based on the classical r‐K dichotomy, but enriched with more modern concepts from community and evolutionary ecology. Both groups participate in the assembly of known animal, plant, and microbial communities, but with different requirements about environmental fluctuations. The so‐called "civilized" organisms are doted with efficient anticipatory mechanisms, allowing them to optimize from an energetic point of view their performances in a predictable environment (stable or fluctuating cyclically at the scale of life expectancy), and they developed advanced specializations in the course of evolutionary time. On the opposite side, the so‐called "barbarians" are weakly efficient in a stable environment because they waste energy for foraging, growth, and reproduction, but they are well adapted to unpredictably changing conditions, in particular during major ecological crises. Both groups of organisms succeed or alternate each other in the course of spontaneous or geared successional processes, as well as in the course of evolution. The balance of "barbarians" against "civilized" strategies within communities is predicted to shift in favor of the first type under present‐day anthropic pressure, exemplified among others by climate warming, land use change, pollution, and biological invasions. Abstract : Disturbances play a decisive role in the assemblage and evolution of plant, animals, and microbes. Two strategies have been selected according to disturbance level of the environment: "civilized" traits/organisms have anticipatory mechanisms efficient in stable environments, while "barbarian" traits/organisms waste energy, but are efficient in unstable environments. Both categories cohabit in communities, but balance according to disturbance level. Implications for global change are discussed.